A "green" method to detect aflatoxin B1 residue in plant oil based on a colloidal gold immunochromatographic assay. Issue 3 (18th December 2015) - Sun, Qing; Zhu, Zhu; Deng, Qian-min; Liu, Jie-min; Shi, Guo-qing
Abstract : Mixing a plant oil and water and then loading the mixture onto an immunochromatographic strip for visual detection of AFB1 in the oil. Abstract : A "green", simple, fast and sensitive method for detecting aflatoxin B1 (AFB1 ) in plant oil was developed based on a colloidal gold immunochromatographic assay. Anti-AFB1 antibody-coated gold colloids were used as detection probes for the immunological recognition of AFB1 . Unlike the traditional methods that require use of organic solvents and complex sample pre-treatment processes, the detection of AFB1 residue in this work was achieved by a "green" process involving simply mixing oil and water in the indicated ratio and then loading the mixture onto the test strip for visual inspection. The visual detection limit of the test strip for AFB1 in oil was 1.5 μg kg −1 and the analysis could be completed in 5 min. Recoveries for AFB1 in five oil samples were within the range of 88.7–122.3% according to a semiquantitative analysis. The results of the test strip were in good agreement with those of HPLC. This test strip can be applied to the household detection of AFB1 in plant oil.